Effect of midazolam, propofol, and dexmedetomidine on postoperative cognitive dysfunction after cardiac surgery in the elderly - Mofeed A Abdelmaboud (Wolters Kluwer Medknow Publications, 2019)
Background Postoperative cognitive dysfunction (POCD) is among the most prevalent and serious life-threatening postoperative complications. Aim The primary outcome was to compare the efficacy of dexmedetomidine, propofol, and midazolam on prevention of POCD during cardiac surgery in the elderly. The secondary outcome is to determine possible complications during the first postoperative day. Patients and methods Ninety elderly patients undergoing cardiac surgery were randomly divided during the cardiopulmonary bypass period into three equal groups. group M: received midazolam 0.1 mg/kg/h, group P: received propofol 1 mg/kg/h, and group D: received dexmedetomidine 0.5 µg/kg/h. Mini-Mental State Examination (MMSE), incidence of POCD, and interleukin 6 (IL-6) were recorded on the day before surgery (M0, F0, L0, respectively), 1 h after extubation (M1, F1, L1, respectively), and 1 week postoperatively (M2, F2, L2, respectively). POCD was diagnosed when the MMSE score decreased two points or more from the preoperative value. Adverse effects (hypotension, bradycardia, laryngospasm, postoperative nausea and vomiting, and hypertension) were recorded. Results As regards MMSE, there were no significant differences among groups except at M1 where it was higher in group D than the other two groups. In groups M and P only, MMSE was significantly higher at M1 than M0 and returned to near preoperative value at M2 in the same group. There were no significant differences regarding the incidence of POCD at F0, F1, and F2. There were no significant differences with respect to blood IL-6, among groups except at L1 where it was significantly higher in both group M and group P than group D. In groups M and P only, IL-6 was significantly higher at L1 than L0 and then returned to near preoperative value at L2 in the same group. Conclusion Dexmedetomidine was a good choice for reducing POCD in cardiac surgery in elderly patients with less side effects.